Improving the energy density of Li-ion capacitors using polymer-derived porous carbons as cathode - Puthusseri, Dhanya; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra (Electrochimica Acta, 2014)
High energy density Li-ion hybrid electrochemical capacitors (Li-HEC) are fabricated with 3 D architectured high surface area porous carbon (HSPC) derived from the poly(acrylamide-co-acrylic acid) potassium salt in a single step without any activating agent. The obtained HSPC exhibits high specific surface area of 1490 m(2) g(-1) and characterized with several analytical techniques. Li-HEC is fabricated with insertion type Li4Ti5O12 anode by adjusting the mass balance based on the single electrode performance with Li. The Li-HEC delivered the maximum energy density of similar to 55 Wh kg(-1), which is much higher than commercially available activated carbon (similar to 36 Wh kg(-1)). Further HSPC based Li-HEC delivered excellent cycleability and rendered similar to 87% of initial value after 2000 cycles. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: energy density; Li-ion hybrid electrochemical capacitors; non-aqueous; porous carbon